Clinical and CT features of ovarian torsion in infants, children and adolescents. Issue 3 (17th March 2021) - Li, Dumin; Zhang, Jingwen; Kiryu, Shigeru; Zhang, Xiaoming; Wang, Fang
Abstract: Objective: To investigate the clinical features and computed tomography (CT) findings of pediatric ovarian torsion. Methods: A retrospective analysis of the clinical and CT data of 61 newborns, infants, children, and adolescents with ovarian torsion confirmed by histopathology was performed. Results: Clinical features included abdominal mass, abdominal pain, nausea and vomiting, and fever. The tumor marker α‐fetoprotein was increased in five cases. Ovarian enlargement was found in 26 cases, and follicles were detected in the peripheral region of the ovary in 21 cases. Twenty‐one cases presented as solid mixed‐density masses on CT images. A total of 30 cases of ovarian torsion were associated with a benign ovarian mass. Among 27 cases of cystic or predominantly cystic masses, the mass had a thickened wall in 26 cases and showed an uneven density in 23 cases. Among all 61 patients, a torsed pedicle was detected in 47 cases. A torsed ovary or mass exhibited mild contrast enhancement in seven cases. Uterine deviation toward the involved side, blurred fat space around lesions, and pelvic free fluid were also found. Conclusion: Pediatric ovarian torsion presents a relatively characteristic CT appearance. Correct diagnosis can be established based on clinical and imaging features. Abstract : Pediatric ovarian torsion presents a relatively characteristic computed tomography appearance. Based on clinical and imaging features, correct diagnosis can be established.